Effect of epidemiology batch posting in improving attitude towards research among medical students - P., Aparnavi; U., Venkatesh; S., Priyanka; S., Shalini (International Journal Of Community Medicine And Public Health, 2020)
Background: Epidemiology batch posting (EBP) is conducted only in a few Indian medical colleges for undergraduate students to orient them with research methodologies. EBP is designed to overcome the lacuna in knowledge on attitude towards scientific research amongst medical students. The objective of the study was to study the effect of EBP in improving attitude towards research among medical students. Methods: A pre-post study was conducted on a batch of 40 students (consecutive sampling technique) posted for EBP in Department of Community Medicine, at VMMC and Safdarjung Hospital, New Delhi during October-November 2017. This was well above the required sample size of 16 calculated using G Power 3.1. Data was collected using R-ATR (revised attitude towards research) Data was found to be non-parametric by applying tests of normality. Hence Wilcoxon sign rank test was used to find the statistical significance in change of attitude between pre and post-tests. Results: Participants mean age was 20.50±1.58 yrs and 75% of them were males. The median attitude towards research usefulness increased from 5.25 to 6.75 following EBP. In the domain of positive predisposition towards research, there was an overall positive change in attitude from a median of 4.00 to 5.25. A negative change was shown in ‘research anxiety’ domain, from a median score of 5.00 to 3.00. Conclusions: Authors recommend that Indian medical curriculum should mandate a small group learning model such as EBP for all undergraduate medical students to bring about a positive attitude towards research and to reduce their anxiety levels.